Occupational Stress and Role Performance-expectation Gap Amongst Teachers of OUAT, Bhubaneswar - Maitreyee Tripathy; Bishnupriya Mishra, Debi Kalyan Jayasingh,Avisweta Nandy (Indian Journal of Extension Education, 2022)
The study was conducted in two colleges of Odisha University of Agriculture and Technology, Bhubaneswar viz. College of Agriculture and College of Agricultural Engineering, Bhubaneswar in 2019 to measure occupational stress of teachers working in the university. Total hundred number of respondents viz. sixty from college of agriculture and forty from college of agricultural engineering were selected following complete enumeration method. Data was collected from the respondents by implementing personal interview method. Profile characteristics of respondents, distribution of respondents according to student’s behaviour, distribution of respondents according to occupational stress, association of occupational stress with the profile characteristics of teachers, the gap between role performance and role expectation of teachers were measured. Educational qualification and present job experience found to be positively correlated with occupational stress of teachers. The maximum gap between the role expectation and role performance of teachers of OUAT was found for the factor; opportunity to earn money, wealth and property followed by delegation of authority, whereas minimum gap was observed in case of job security. Total deviation of 23.97 per cent was found between role expectation and role performance of teachers of OUAT.